2023
DOI: 10.3390/nu15051275
|View full text |Cite
|
Sign up to set email alerts
|

Use of Caffeine-Containing Energy Drinks by Japanese Middle School Students: A Cross-Sectional Study of Related Factors

Abstract: Excessive consumption of caffeine negatively affects individuals’ health. Therefore, we studied the use of energy drinks and the conditions associated with it among Japanese secondary school students. Participants were 236 students in grades 7–9 who completed anonymous questionnaires at home in July 2018. We measured the basic attributes and dietary, sleeping, and exercise habits. We used Chi-squared tests to compare differences between users and non-users of energy drinks. Logistic regression analyses were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In this study, we found that energy drink intake mainly shortened the calculation time during the task but did not decrease the number of errors, which is consistent with previous studies ( , 2020). Energy drinks actually affect some aspects of performance (calculation time) but not all (decrease the number of errors during calculation), which is felt as a positive effect of energy drinks for some people, such as adolescent males, and they frequently drink them (Yamasaki et al, 2023). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we found that energy drink intake mainly shortened the calculation time during the task but did not decrease the number of errors, which is consistent with previous studies ( , 2020). Energy drinks actually affect some aspects of performance (calculation time) but not all (decrease the number of errors during calculation), which is felt as a positive effect of energy drinks for some people, such as adolescent males, and they frequently drink them (Yamasaki et al, 2023). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that energy drinks improve the performance during reaction-time, tapping, executive function (reaction time plus tapping) tasks, and cognitive performance (Pomportes et al, 2019, Lassiter et al, 2012, Oliver et al, 2021. It has also been reported that adolescent males feel that energy drinks are effective (Temple et al, 2011) and they consume more than adolescent female (Yamasaki et al, 2023). However, excessive consumption of energy drinks induces arrhythmia and cardiovascular diseases, which may cause sudden death, sleep disorders and anxiety, hepatitis, and acute kidney injury (Costantino et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, as well as in previous studies, participation in sports was associated with increased consumption of junk food (sugar-sweetened beverages) [44], suggesting that specific adverse effects associated with extracurricular activities exist. High school students should understand which appropriate snacks and beverages can improve bone density [45].…”
Section: Discussionmentioning
confidence: 99%